Challenges of teaching outdoors in the Romanian core procurement cycle - Torkos, Henrietta; Egerau, Anca (Technium Social Sciences Journal, 2022)
In the formal and non-formal educational systems in Romania, outdoor education has been a subject of great interest in the last few years. However, its use, was highly debated, because of the lack of knowledge on the topic, lack of information on the benefits, and mostly the fear of confronting the challenges that come with its implementation. This last challenge, comes into account because of the lack of a specific frame regarding this topic in the scholar national curriculum. The present article, presents the main challenges that can come with the implementation of outdoor education and its activities in the frame of the formal educational system, at the level of core procurement cycle. In the study, there is an analysis on the main elements of outdoor education that are present in the scholar curriculum at this level. Also, it presents the results of a brief research on the beliefs of primary school teachers from Arad County, on the most important challenges that they face when implementing outdoor learning activities in schools. The research was made using the survey method, with the use of the instrument: questionnaire, in the school year 2020-2021, on a number of 77 teachers.